Polyclonal non multiresistant methicillin resistant Staphylococcus aureus isolates from clinical cases of infection occurring in Palermo, Italy, during a one-year surveillance period - Mammina Caterina; Calà Cinzia; Bonura Celestino; Di Carlo Paola; Aleo Aurora; Fasciana Teresa; Giammanco Anna (BMC, 2012)
Abstract Background The evolving epidemiology of methicillin resistant Staphylococcus aureus (MRSA) is characterized by the emergence of infections caused by non multiresistant MRSA carrying staphylococcal chromosomal cassette (SCC)mec IV or V in the healthcare settings. A molecular epidemiological analysis of non multiresistant MRSA isolates from four acute general hospitals was performed in Palermo, Italy, during a one year period. Methods For the purpose of the study, MRSA isolates were defined as non multiresistant when they were susceptible to at least three classes of non β-lactam antibiotics. Seventy-five isolates were submitted to antimicrobial susceptibility testing, multilocus sequence typing (MLST) and polymerase chain reaction (PCR) for SCCmec, accessory gene regulator (agr) groups, arginine catabolic mobile element (ACME) and Panton Valentine leukocidin (PVL) toxin genes. For epidemiological typing, Multiple-Locus Variable-Number Tandem Repeat Fingerprinting (MLVF) was performed on all isolates and pulsed field gel electrophoresis (PFGE) on ST8 isolates. Results Non multiresistant MRSA isolates were isolated from all hospitals. Resistances to ciprofloxacin, macrolides and tetracycline were the most prevalent. MLST attributed 46 isolates with ST22, 13 with ST8, eight with ST1, three with ST50 and three with ST398. SCCmec type IV was found in all isolates. PVL was detected in one ST22 isolate. All isolates tested negative for the ACME element. MLVF identified 31 different patterns, some subtype clusters ranging in size between two and 22 isolates. The closely related PFGE patterns of the ST8 isolates differed from USA300. Conclusions A polyclonal circulation of non multiresistant MRSA along with blurring of boundaries between healthcare associated (HA)-MRSA and community associated (CA)-MRSA appear to be occurring in our epidemiological setting. A better understanding of spread of MRSA with the support of molecular typing can provide invaluable information in the epidemiological, microbiological and clinical fields.